Engineering of a microbial coculture of Escherichia coli strains for the biosynthesis of resveratrol. Issue 1 (December 2016) - Camacho-Zaragoza, José; Hernández-Chávez, Georgina; Moreno-Avitia, Fabian; Ramírez-Iñiguez, René; Martínez, Alfredo; Bolívar, Francisco; Gosset, Guillermo
Abstract Background Resveratrol is a plant natural product with many health-protecting effects which makes it an attractive chemical both for academic studies and industrial purposes. However, the low quantities naturally produced by plants as well as the unsustainable procedures of extraction, purification and concentration have prompted many biotechnological approaches to produce this chemical in large quantities from renewable sources. None of these approaches have considered a microbial coculture strategy to produce this compound. The aim of this study was to prove the functionality of a microbial coculture for the biosynthesis of resveratrol. Results In this work, we have successfully applied a coculture system strategy comprised of two populations ofEscherichia coli strains, each with a partial and complementary section of the pathway leading to the biosynthesis of the stilbene resveratrol. The first strain is apheA knockout mutant previously engineered to excrete p-coumaric acid into the medium through the overexpression of genes encoding a tyrosine ammonia lyase fromRhodothorula glutinis, a feedback resistant 3-deoxy-D-arabino -heptulosonate 7-phosphate synthase and a transketolase. The second strain in the coculture was engineered to express the second part of the resveratrol biosynthetic pathway through the introduction of synthetic genes encoding the 4-coumaroyl-CoA ligase fromStreptomyces coelicolor A2 and the stilbene synthase either from the peanutArachis hypogaea or the grapevineVitis vinifera, the latter synthesized employing a gene harmonization strategy and showing better resveratrol production performance. Batch cultures were performed in mineral medium with glycerol as the sole carbon source, where a final titer of 22.6 mg/L of resveratrol was produced in 30 h. Conclusions To our knowledge, this is the first time that a coculture of bacterial strains is used for the biosynthesis of resveratrol from glycerol, having the potential for a greater improvement in the product yield and avoiding the use of precursors such as p-coumaric acid, yeast extract or an expensive inhibitor such as cerulenin.